A CONTRACT REVIEWED FROM THE PERSPECTIVE OF CIVIL LAW IN INDONESIA MAY BE DELAYED DUE TO FORCE MAJEURE - Kurniawan , Ri˚zki; Noer, Zakiah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
The aim of this study is to: Recognize the structure of an emergency clause (force majeure) in a contract; and Recognize the legal implications for the parties involved and the actions that need to be taken in the event that an emergency (force majeure) nullifies a contract. In this study, the author used three distinct methodologies, conceptual, legislative, and comparative. However, in order to fulfill their responsibilities under a contract or agreement, the parties must be able to prove that they are faced with legitimate obstacles